Comparative Analysis of Direct Instruction and Practicum-Based Learning on Students’ Learning Outcomes - Suharli AJ; Isnania Isnania; Susan Meiliasari; Nilam Cahyati (LP2M UIN Ambon, 2026)
Physics learning plays an important role in developing logical and analytical thinking skills, but still faces obstacles due to its abstract nature, dominant theory, and minimal experimental activities. On the other hand, the Direct Instruction model offers systematic and structured material delivery, while practicum-based learning provides more concrete empirical experiences. This study aims to compare the effectiveness of the two approaches on student learning outcomes. The method used is quantitative descriptive with a Quasi-Experimental Non-Equivalent Control Group Design. The sample was selected through a purposive sampling technique involving 16 students each in the experimental and control classes. The research instruments were a pre-test and a post-test consisting of 10 multiple-choice questions on the material of density and hydrostatic pressure. Data analysis was carried out through normality tests, N-Gain calculations, and Mann–Whitney U tests using the IBM SPSS Statistics 26 application. The results showed a significant difference, where practicum learning was more effective in improving student learning outcomes than direct learning. Therefore, practical-based learning helps students understand concepts better and involves student activities.